Dirac CP violation phase in the neutrino sector with A4 flavour symmetry - Phi, Quang Van; Nguyen, Anh Ky; Tran, Tien Manh (Communications in Physics, 2024)
CP violation is one of the problems of the physics beyond the Standard Model. It can happen in both the quark and the lepton sectors. In the present paper, following the work arXiv:1602.07437 [hep-ph], this problem is re-considered in the lepton sector (neutrino subsector) within an extended Standard Model with an A_4 flavour discrete symmetry with a new and more convenient parametrization. As a result, a perturbative mixing matrix is derived. Then, the Dirac CP violation phase \(δ_CPδ\) and the Jarlskog invariant \(J_CPJ\) are analytically obtained from theoretically derived equations leading to the solutions \(δ= ± 12π\) . Between the two solutions, the solution \(δ=-12π\) (i.e., \(32π\)) is more preferable as it is more consistent with the experimental data for the inverted ordering of the neutrino masses for the gobal fit [PDG] or the normal ordering [T2K, NO\( u\)A]). A relation between δ and J is also given in terms of new parameters. The maximum value of Jarlskog invariant \(|J^max|\) is found in the range 0.0237 < |J^max| < 0.034, covering the 2022-2023 global fit values [PDG]: \(|J_PDG^max|= 0.0336± 0.0006 (± 0.0019)\) at \(1σ (3σ\)). Other values of J can be determined by the ralation \(J (δ)\) and approximated by Fig. 2. between two solutions.